A review on aviation restructuring action to survive in COVID-19 challenges: Malaysia perspective - Ariffin, Ahmad Hamdan; Yaakub, Mohd Fauzi (Penerbit UTHM, 2020)
Aviation is the most affected by the global outbreak of COVID-19, as traffic has almost ceased, causing airlines to be completely grounded, placing them in severe financial distress. The survival of airlines, indeed, the landscape of the domestic and global aviation industry at the end of the crisis, is still unfolding. As few months passed since the Movement Control Order (MCO commenced, Malaysia has successfully flattened the curve for infections in this country by conducting acute case detections and screen those who in high risk group such as Malaysians returning from overseas and so on. Malaysia has slowly reopened its economy sector to allow businesses resumed with strict Standard Operation Procedures (SOP) to be followed. Therefore, this chapter will review the action that airlines and airport management in Malaysia had revised its financial strategies to recover quickly from the losses over past few months.